Putting learning at the centre: Adaptive development programming in practice - Valters, Craig; Cummings, Clare; Nixon, Hamish (ODI, 2016)
Adaptive programming suggests, at a minimum, that development actors react and respond to changes in the political and socio-economic operating environment. It emphasises learning and the development practitioner is encouraged to adjust their actions to find workable solutions to problems that they may face. Being prepared to react to change may seem like common sense – and indeed it is. However much development thinking and practice remains stuck in a linear planning model which discourages learning and adaptation, in part because projects are seen as ‘closed, controllable and unchanging systems’ (Mosse, 1998: 5). This paper critically engages with this problem and makes clear why and how learning needs to be at the centre of adaptive development programming. It begins by clarifying why and what kind of learning matters for adaptive programming. The paper then turns its focus to how strategies and approaches applied throughout a programme’s conception, design, management and M&E can enable it to continually learn and adapt.
Keywords: IMPORTANT

Learning and adaptation: 6 pitfalls to avoid - Valters, Craig (Devex, 2016)

‘Learning journeys’ for adaptive management – Where does it take us? - Ørnemark, Charlotte (GPSA Note 12, 2016)
Keywords: IMPORTANT

From analysis to action: operationalising learning and adaptation in Savings at the Frontier - Salehi, Yusef (2016)
Keywords: IMPORTANT

Exploring ways to reconcile accountability and learning in the evaluation of niche experiments - Regeer, Barbara J.; de Wildt-Liesveld, Renée; van Mierlo, Barbara; Bunders, Joske F. G. (Evaluation, 2016)
While evaluation is seen as a mechanism for both accountability and learning, it is not self-evident that the evaluation of niche experiments focuses on both accountability and learning at the same time. Tensions exist between the accountability-oriented needs of funders and the learning needs of managers of niche experiments. This article explores the differences in needs and expectations of funders and managers in terms of upwards, downwards and internal accountability. The article shows that as the multi-stakeholder contexts in which niche experiments take place give rise to various requirements, tensions in evaluation are essentially a specific manifestation of tensions between niche experiments and their multiple contexts. Based on our findings, an adjusted accountability framework is proposed, including several strategies that can reconcile a learning approach with accountability needs in niche experiments aiming to change current practices in a more sustainable direction.

Assumption-aware tools and agency; an interrogation of the primary artifacts of the program evaluation and design profession in working with complex evaluands and complex contexts - Morrow, Nathan; Nkwake, Apollo M. (Evaluation and Program Planning, 2016)
Like artisans in a professional guild, we evaluators create tools to suit our ever evolving practice. The tools we use as evaluators are the primary artifacts of our profession, reflect our practice and embody an amalgamation of paradigms and assumptions. With the increasing shifts in evaluation purposes from judging program worth to understanding how programs work, the evaluator’s role is changing to that of facilitating stakeholders in a learning process. This involves clarifying purposes and choices, as well as unearthing critical assumptions. In such a role, evaluators become major tool-users and begin to innovate with small refinements or produce completely new tools to fit a specific challenge or context. We interrogate the form and function of 12 tools used by evaluators when working with complex evaluands and complex contexts. The form is described in terms of traditional qualitative techniques and particular characteristics of the elements, use and presentation of each tool. Then the function of each tool is analyzed with respect to articulating assumptions and affecting the agency of evaluators and stakeholders in complex contexts.
Keywords: Agency; Assumption-aware; Complex context; Complex programs; Participatory approaches; Program design; Program evaluation; Program tools; Theory-based

Experiential Learning: Fostering lasting behavioural change - Norton, Brittney M. (Prospects practice paper, 4, 2016)
The term ‘experiential learning’ is often mistakenly used to describe any learning experience that involves participatory activities. This paper presents an overview of what true experiential learning is and how this form of learning allows for real-world application - thus promoting lasting behavioural change. Furthermore, it explains how experiential learning was adopted as the methodological core of the Prospects psychosocial programme in Liberia, which builds ‘pre-employment skills’ in 3,500 vulnerable youth aged 15-24 years. The goal of the paper is to provide other youth and education development practitioners with a resource that can be used to strengthen youth and behaviour change programmes through the incorporation of the experiential learning theory. In addition, this paper explains its application in the Prospects programme, before concluding with key considerations of such a design. 1